Socio-cultural Impacts of Rural Tourism on Caste-diversified Communities along Annapurna Sanctuary Trail (AST), Nepal - Tiwari, Surendra; Thapa, Ajay; Nguyen, Thi Phuoc Lai; Timilsina, Jagat (Journal of Development and Social Engineering, 2024)
Rural tourism is widely recognized as a culturally sensitive approach to preserving cultural heritages and traditions at the local level. However, in practice, it brings both benefit and cost to the host community. Based on 120 household surveys, five key informant interviews, and field observations in the culturally and ethnically diversified rural communities along Nepal’s Annapurna Sanctuary Trail, this study examined the perceived socio-cultural impacts of rural tourism. The findings revealed both positive and negative impacts on the cultural and social dynamics of rural communities. While rural tourism has enhanced gender equality, social cohesion, community empowerment, and social inclusion along with social services and infrastructure, it has also threatened local traditions, culture, and architectural heritage. The primary objective of preserving local cultural heritage has only been partially achieved, contributing to a cultural identity crisis. Unregulated private construction exacerbates the difficulties in maintaining cultural integrity. The study suggests that concerned authorities should prioritize cultural heritage preservation for the sustainability of the socio-cultural aspects of rural tourism in the region.